Financial Performance Of Islamic Insurance Companies Before And During The Covid-19 Pandemic - Aulia Dika Zahra; Ahmad Baehaqi; Prayogo P. Harto (LPPM ISNJ Bengkalis, 2023)
This research aims to analyze the comparative financial performance of Islamic insurance companies before and during the Covid-19 pandemic. The financial performance measured refers to the early warning system ratios, which consist of the underwriting, liquidity, own retention, premium stability, and loss ratios. This research is a descriptive quantitative research using the Wilcoxon test. The research population is all Islamic insurance companies registered with the Financial Services Authority (FSA) for 2018-2021. The sample was selected based on purposive sampling so that 48 observation data were obtained. Data comes from financial reports obtained through the official FSA and Company websites. The research results show significant differences in financial performance before and during the pandemic in the liquidity and loss ratio variables. However, there is no significant difference in financial performance before and during the pandemic in the underwriting ratio, own retention ratio, and premium stability ratio variables. This research can complement existing theories and become a reference for companies to evaluate and improve their financial performance, especially after the Covid-19 pandemic.